Identification of off-site construction disputes: technical, managerial and external dispute causes - Yildiran, Merve Pelinsu; Demirdogen, Gokhan (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeWhile off-site construction (OSC) offers a promising solution to many problems plaguing traditional construction (e.g. low productivity, waste and safety risks), a lack of standards and knowledge about OSC, especially regarding disputes, hinders its wider adoption. This study aims to address this gap by identifying and analyzing the importance levels of technical, managerial and external disputes specific to OSC projects.Design/methodology/approachThree steps methodology was employed in the study. Focus group discussion (FGD) technique was used to identification and finalize dispute causes found from literature and collect data for the next step. In the study, two multi-criteria decision-making MCDM (methods) [a hybrid approach-Pythagorean fuzzy analytic hierarchy process (AHP) and fuzzy Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS)] were employed. While Pythagorean fuzzy AHP was used to calculate the weights of criteria, fuzzy TOPSIS analysis was used to calculate the weights of main and sub-dispute causes. Instead of using the classical AHP method, the Pythagorean fuzzy AHP method was employed due to its superiority in capturing the inherent uncertainty and ambiguity of decision-makers, giving flexibility to decision-makers with linguistic variables instead of expecting exact evaluation scores and flexibility in the integration with other methods. During the analysis of the weights of the main and sub-dispute causes, the fuzzy TOPSIS method was preferred. The fuzzy TOPSIS method involves a quicker and more straightforward decision-making process. Also, the fuzzy TOPSIS method allows the consideration of numerous alternatives and evaluation criteria and uncertainty in the decision-making process.FindingsThe analysis reveals that technical disputes pose the biggest challenge in off-site construction compared to managerial or external disputes. Specifically, late completion, delivery and installation of components emerged as the most significant technical dispute. Within managerial disputes, poor planning and management of the project ranked highest, while the complexity of legal expressions was the most prominent external dispute factor.Originality/valueIn the literature, three studies offer some insight on OSC disputes by analyzing the litigation cases. Nonetheless, the results can be misleading, because some disputes can be resolved before the litigation process. Therefore, the study findings can aid in foreseeing technical, managerial and external factors and in generating robust OSC contracts by considering these issues.
Keywords: Off-site construction; Financial disputes; Contractual disputes; FUZZY TOPSIS; PERFORMANCE EVALUATION; SELECTION; AHP; BARRIERS; INDUSTRY; PROJECTS; MODEL; Engineering; Business & Economics